The National University of Engineering as cultural manager of its archaeological heritage during the period 2017-2022 - Molina Vilca, Isabel Cristina (2024)
The National University of Engineering (UNI), located in the district of Rímac, Lima, manages three pre-Hispanic archaeological monuments: Huaca UNI-Cismid, Huaca UNI-Minas and Huaca Candela. This article seeks to characterize the heritage management of these huacas between 2017 and 2022, analyzing the management frameworks, the actors involved, the heritage values and the perception of the university community, in addition to presenting suggestions for improvement proposed by this group. The research used a mixed approach, with a non-experimental cross-sectional design, exploratory scope and non-probabilistic sampling, applying techniques such as bibliographic collection, interviews and questionnaires. It is concluded that the heritage management of the UNI huacas is in an incipient state, where the main actors are the university community and the academy, and a notable lack of knowledge and low appreciation of these monuments persists.